Evaluation of the effective time for GSK-3 inhibition in experimental autoimmune encephalomyelitis mouse model by tideglusib (NP-12) in preventing neuroinflammation - Al-Zaidi, Ahmed Salam (2018)
Glycogen synthase kinase-3 (GSK-3) is an enzyme involved in various neurodegenerative and neuro-inflammatory diseases, including multiple sclerosis (MS) and its animal model of experimental autoimmune encephalomyelitis (EAE). The severity of the disease could be characterized by the degree of cellular invasion to the central nervous system (CNS) and demyelination that partly mediated by Th1 and Th17 effector cells. The present study is to investigate the efficacy of GSK-3 inhibition at a different course of treatment in ameliorating disease progression. This study also aims to evaluate the effects of GSK-3 inhibition to central neuro-invasion and demyelination. Female C57BL/6 mice were induced with myelin oligodendrocyte glycoprotein (MOG35-55) in conjunction with complete freund's adjuvant (CFA) and pertussis toxin. Inhibition of GSK-3 is performed by the administration of NP-12, a small heterocyclic Thiadiazolidinones (TDZD), intraperitoneally during pre-EAE induction, on the same day, and post-EAE. Data revealed that NP-12 delivery during pre-EAE induction greatly protected the mice from EAE, delayed the onset of EAE symptoms by 7 days from day-14.3 ± 0.5 (in EAE mice) until day-21.3 ± 3.2 (in the treated mice). Furthermore, NP-12 treated-EAE mice had notably reduced the inflammatory cells infiltration and axonal damage (demyelination) in the spinal cord. Inhibition of GSK-3 also abrogated the production of Th1, Th9 and Th17 associated cytokines but, increases the production of IL-4 level to 1790 ± 95.0 pg/mL compare to EAE 480 ± 38.0 pg/mL and in IL-10 780 ± 22.0 pg/mL compared to EAE 410 ± 16.0 pg/mL. These data demonstrate the effectiveness of NP-12 at a different time course of administration to reduce the severity of EAE disease and protect the CNS environment from potential cellular invasion or demyelination, thus, suggests the potential use of GSK-3 inhibitor in the treatment of EAE.